High prevalence and genetic diversity of hemoplasmas in bats and bat ectoparasites from China - Rui Wang; Ze-Min Li; Qiu-Ming Peng; Xiao-Lan Gu; Chuan-Min Zhou; Xiao Xiao; Hui-Ju Han; Xue-Jie Yu (One Health, 2023)
Hemoplasmas can cause severe hemolytic anemia in humans. To explore the genetic diversity and the potential transmission routes of hemoplasmas among bat population, bats and bat-ectoparasites including bat-flies, bat-mites, and bat-ticks were collected in Eastern and Central China from 2015 to 2021, and tested with PCR for hemoplasmas 16S rRNA gene. Based on 16S rRNA PCR, 18.0% (103/572) adult bats were positive for hemoplasmas, but none of 11 fetuses from hemoplasmas-positive pregnant bats was positive for hemoplasmas. These results indicated that adult bats had a high prevalence of hemoplasma, but vertical transmission of hemoplasmas did not occurr in the bats. Based on the 16S rRNA gene PCR, the minimum infection rate of bat-ectoparasite for hemoplasmas was 4.0% (27/676), suggesting that bat-ectoparasite also had a high prevalence for hemoplasmas. Phylogenetic analysis revealed that bat hemoplasmas from this study clustered into 4 genotypes (I-IV). Genotype I clustered together with hemoplasmas identified in bats from America. Genotype II shared high similarity with a human-pathogenic hemoplasma Candidatus Mycoplasma haemohominis. Genotype III and IV were unique, representing 2 new hemoplasma genotypes. Only genotype I was identified in both bats and all bat-ectoparasites including bat-flies, bat-mites, and bat-ticks. In conclusion, bats and bat-ectoparasites from China harbored abundant genetically diverse hemoplasmas including potential human-pathogenic hemoplasmas, indicating bats and bat-ectoparasites may play important roles in the maintenance and transmission of hemoplasmas in the natural foci.